2022
DOI: 10.3390/ijms23052492
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Gastric Epithelial Cells Resist CagA Delivery by the Helicobacter pylori Type IV Secretion System

Abstract: The initial step in bacterial infection is adherence of the bacterium to the target cell surface. Helicobacter pylori exploits the interaction of bacterial adhesin protein HopQ with human epithelial CEACAMs (CEACAM1, 5, and 6) to stably adhere to gastric epithelial cells, which is necessary for delivery of the H. pylori CagA oncoprotein into the epithelial cells via a type IV secretion system. In contrast to human CEACAMs, however, HopQ does not interact with Ceacam1 (mouse CEACAM1) in vitro or in CHO cells ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Given this, we next conducted an infection study of adult mice with cagA + H. pylori. However, we subsequently noticed that mouse gastric epithelial cells resist H. pylori-mediated CagA injection because of the incompatible interaction of H. pylori adhesin HopQ with mouse Ceacam proteins (49)(50)(51).…”
Section: Establishment Of Transgenic Mice That Inducibly Express Caga...mentioning
confidence: 99%
“…Given this, we next conducted an infection study of adult mice with cagA + H. pylori. However, we subsequently noticed that mouse gastric epithelial cells resist H. pylori-mediated CagA injection because of the incompatible interaction of H. pylori adhesin HopQ with mouse Ceacam proteins (49)(50)(51).…”
Section: Establishment Of Transgenic Mice That Inducibly Express Caga...mentioning
confidence: 99%
“… 168 Moreover, mouse gastric epithelial cells are resistant to the actions of CagA due to the inability of HopQ to bind to mouse CEACAMs. 169 The loss of Cag T4SS activity in vivo, combined with resistance of mouse cells to CagA activity, may account at least in part for the absence of gastric cancer or gastric ulceration in H. pylori -infected wild-type mice.…”
Section: Activities Of Caga and The T4ss In Animal Modelsmentioning
confidence: 99%
“…A recent study noted that the instability of the relationship between H. pylori HopQ and mouse CEACAMs may explain why the pathogenesis of infection in the stomach of rodents infected with CagA positive H. pylori strains occurs differently from infection by the same strain in humans. The authors also demonstrated that the presence of functional T4SS is associated with a time-dependent reduction in human CEACAM1 levels after CagA-positive H. pylori infection[ 54 ]. However, it is still unclear whether the instability of the HopQ–CEACAMs relationship favors the host or the bacterium, so more studies are needed to investigate the possibility of these interactions being beneficial in favor of the patient infected with H. pylori.…”
Section: Caga — H Pylori Translocated Oncoproteinmentioning
confidence: 99%